The affair of the mysterious letter - Hall, Alexis J. (Ace, 2019)
"Upon returning to the city of Khelathra-Ven after five years fighting a war in another universe, Captain John Wyndham finds himself looking for somewhere to live, and expediency forces him to take lodgings at 221b Martyrs Walk. His new housemate is Ms. Shaharazad Haas, a consulting sorceress of mercurial temperament and dark reputation. When Ms. Haas is enlisted to solve a case of blackmail against one of her former lovers, Miss Eirene Viola, Captain Wyndham finds himself drawn into a mystery that leads him from the salons of the literary set to the drowned back-alleys of Ven and even to a prison cell in lost Carcosa. Along the way he is beset by criminals, menaced by pirates, molested by vampires, almost devoured by mad gods, and called upon to punch a shark. But the further the companions go in pursuit of the elusive blackmailer, the more impossible the case appears. Then again, in Khelathra-Ven reality is flexible, and the impossible is Ms. Haas' stock-in-trade"--